2021
DOI: 10.3390/nu13093061
|View full text |Cite
|
Sign up to set email alerts
|

Irritable Bowel Syndrome, Depression, and Neurodegeneration: A Bidirectional Communication from Gut to Brain

Abstract: Patients with irritable bowel syndrome (IBS) are increasingly presenting with a wide range of neuropsychiatric symptoms, such as deterioration in gastroenteric physiology, including visceral hypersensitivity, altered intestinal membrane permeability, and gastrointestinal motor dysfunction. Functional imaging of IBS patients has revealed several abnormalities in various brain regions, such as significant activation of amygdala, thinning of insular and anterior cingulate cortex, and increase in hypothalamic gray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 122 publications
(165 reference statements)
2
37
0
10
Order By: Relevance
“…The study of the effects of the gut microbiome on behavior and neurobiology, known as the MGBA, began with observations on patients with IBS [30]. IBS is characterized by abdominal pain and changes in bowel habits.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the effects of the gut microbiome on behavior and neurobiology, known as the MGBA, began with observations on patients with IBS [30]. IBS is characterized by abdominal pain and changes in bowel habits.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the wide range of neuropsychiatric symptoms co-occurring in IBS could suggest common pathophysiological pathways of action or bidirectional potentiation of gastrointestinal, non-gastrointestinal, and socio-affective symtompatology. In this context, Aziz et al [24] and Cafer and Okan [14], respectively, showed that affective behaviour and sleep regulating brain areas changes were significantly associated with dysbiosis and IBS all of which could be relevant evidence for anxyiolitic and antidepressant treatments efficiency in IBS-associated symptoms alleviation, as shown by Cafer and Okan [14].…”
Section: Neuropsychiatric Comorbidities In Ibsfrom Start To What End?mentioning
confidence: 98%
“…Table 4 is a summary of the proposed factors as the cause of IBS and their role in the pathophysiology of the disease process of IBS. Serotonin reuptake receptor (SERT) and sucrose isomaltase (SCN5A) have been reported in IBS [17,18].…”
Section: Pathophysiology Of Ibsmentioning
confidence: 99%